O percurso de escolarização de pescadoras e pescadores artesanais na EJA do Pontal – Marataízes/ES – 2014 – 2019 - Pires, Carlos Fagner Pereira (2023)
This study has as its topic “The schooling of artisanal fisherwomen and fishermen in the Youth and Adult Education (EJA) with emphasis on the access, permanence and completion of Basic Education”, due to the low level of school education of this group. It aimed to analyze the schooling path of working students, in particular, from the artisanal fishing segment who seek assistance in the (EJA) of Pontal, Marataízes/ES in the period of 2014-2019. The hypothesis is that the schooling process of artisanal fisherwomen/men has been compromised by the devaluation of their knowledge and experiences by the school and by the dissociation of curricular contents with the production of the lives of these subjects in their fishing job, as well as their relation with the Insurance Artisanal Fisherman Unemployment (SDPA). As a theoretical option, it explores the relationship among the categories of work, education and nature, supported by the thought of Marx, Marx and Engels, Antunes, Freire, Saviani, Nosella, putting into evidence these categories as fundamental in the constitution of the human being, in his interaction with nature, highlighting work as an educational principle. This qualitative research, mediated by participant research and documentary research, used these following instruments and techniques for data collection and production: primary and secondary sources, questionnaires, participant observation, field diary and sharing circles. The research subjects were 15 Youth and Adult Education professionals, 11 artisanal fisherwomen and fishermen students and 22 artisanal fisherwomen/men who live in Pontal’s fishing community. The results put into question the initial hypothesis, since they show that working with fishing activities, leads to the participants´ interruption of the education process, being the main obstacle to the schooling of artisanal fisherwomen/men. They also reveal that the closure of EJA classes and period of the day offering by the municipality constitutes an obstacle in the school path of these students, thus characterizing the denial of the right to education by the public authorities. Pregnancy and marriage are also mentioned as obstacles to schooling. Regarding the SDPA, the results indicate that, although the program involves students and community members as beneficiaries, it does not appear to be an obstacle to the schooling of artisanal fishermen/fishermen.